2021
DOI: 10.3390/cancers13225821
|View full text |Cite
|
Sign up to set email alerts
|

Magnetometer-Guided Sentinel Lymph Node Dissection in Prostate Cancer: Rate of Lymph Node Involvement Compared with Radioisotope Marking

Abstract: Sentinel pelvic lymph node dissection (sPLND) enables the targeted removal of lymph nodes (LNs) bearing the highest metastasis risk. In prostate cancer (PCa), sPLND alone or combined with extended PLND (ePLND) reveals more LN metastases along with detecting sentinel LNs (SLNs) outside the conventional ePLND template. To overcome the disadvantages of radioisotope-guided sPLND in PCa treatment, magnetometer-guided sPLND applying superparamagnetic iron oxide nanoparticles as a tracer was established. This retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…They described a comparable detection rate (98.18% vs. 98.11%, respectively) [54]. Despite the feasibility of the magnetometer-guided technique, this group underlined some contraindications of the magnetic-guided technique in patients bearing pacemakers or other implanted electronic devices, in cases of iron hypersensitivity as well as in hemochromatosis or other iron overload conditions [54]. Moreover, it should be taken into account that the presence of any metal implant or prosthesis may negatively affect the diagnostic yield of the technique.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…They described a comparable detection rate (98.18% vs. 98.11%, respectively) [54]. Despite the feasibility of the magnetometer-guided technique, this group underlined some contraindications of the magnetic-guided technique in patients bearing pacemakers or other implanted electronic devices, in cases of iron hypersensitivity as well as in hemochromatosis or other iron overload conditions [54]. Moreover, it should be taken into account that the presence of any metal implant or prosthesis may negatively affect the diagnostic yield of the technique.…”
Section: Discussionmentioning
confidence: 90%
“…Engels et al presented a retrospective analysis comparing radio-guided SNB and magnetic SNB techniques. They described a comparable detection rate (98.18% vs. 98.11%, respectively) [54]. Despite the feasibility of the magnetometer-guided technique, this group underlined some contraindications of the magnetic-guided technique in patients bearing pacemakers or other implanted electronic devices, in cases of iron hypersensitivity as well as in hemochromatosis or other iron overload conditions [54].…”
Section: Discussionmentioning
confidence: 99%
“…Hypogastric and obturator fossa nodal might be removed for all pN1 patients because of their high incidence of metastases. It was critical to identify the positive lymph node before or during surgery; approximately 7% of lymph node metastases were detected outside the conventional extended LND template ( 23 ). We considered the extent of LND evaluated by risk stratification (mainly Gleason score and T stage in our study) outweighed an ELND template for pN1 PCa patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another promising direction of SLN-centered investigations is the usage of magnetometer-based techniques and SPIONs [109]. The first studies revealed very promising outcomes, although the reliability of magnetometer techniques require further, more thorough studies involving larger cohorts [35,36,110,111].…”
Section: Prostate Cancermentioning
confidence: 99%